The Effect of Social Media Promotion and Word of Mouth on Purchase Decisions at Humaloka Coffee in Bandung City - Reza Ferdiansyah; Putut Raka Santoso (Escalate : Economics and Business Journal, 2026)
Bandung's coffee shop boom heightens MSME competition like Humaloka Coffee, depending on social media promotion and word-of-mouth in digital trends. This study analyzes their effects on purchase decisions via quantitative descriptive-verification survey of 96 non-probability samples from December 2025 visitors, using online questionnaires, observation, interviews, multiple linear regression, classical tests, and SPSS. Results reveal "good" ratings (X1=73.83%, X2=78.71%), equation Y=9.331+0.410X1+0.364X2, partial sig.<0.05 (t=3.391/3.803), simultaneous F=19.102 (sig.=0.000), R²=0.291. Factors synergistically drive decisions (29.1% variance); optimize content and experiences for loyalty.